Implementation of the Value of Religious Moderation in Public Universities to Prevent Radical Understanding Through the Integration of Religious Education Materials - Koko Adya Winata; Sartono Sartono; Uus Ruswandi (Universitas Muhammadiyah Enrekang, 2023)
The emergence of radical understanding among students is allegedly an attempt by Islamic fundamentalists to carry out regeneration with the main target of intellectuals. For this reason, serious efforts are needed from the entire academic community to anticipate the development of radicalism on campus. Understanding the value of religious moderation to students is very important to build a moderate and polite student perspective and religious practice. This article aims to examine the implementation of the value of religious moderation in state universities to prevent radicalism through the integration of religious education materials. The method used in this study is a qualitative descriptive method. Researchers collect data through observation and documentation studies by tracing various expert studies, online and offline newspapers, articles, and published scientific works related to research. Based on the results of the study it was found: there is an opportunity for students to be exposed to radicalism, the role of religious lecturers is very important in preventing radicalism on campus through the development of learning models of religious education, it is necessary to integrate the value of religious moderation with religious education